An investigation of parasitic infections and review of molecular characterization of the intestinal protozoa in nonhuman primates in China from 2009 to 2015. Issue 1 (April 2017) - Li, Junqiang; Dong, Haiju; Wang, Rongjun; Yu, Fuchang; Wu, Yayun; Chang, Yankai; Wang, Chenrong; Qi, Meng; Zhang, Longxian
Abstract: Parasites are a well-known threat to nonhuman primate (NHP) populations, and potentially cause zoonotic diseases in humans. In this study, the basic data was provided of the parasites in NHPs and the molecular characterization of the Enterocytozoon bieneusi, Giardia duodenalis, Cryptosporidium spp., and Entamoeba spp. were reviewed, which were found in these samples. A total of 3349 fecal samples were collected from 34 species reared at 17 districts in zoos, farms, free-range, or research laboratories, and examined microscopically. Eleven genera of intestinal parasites were detected: five genera of protozoans ( Isospora spp., Entamoeba spp., Giardia sp., Cryptosporidium spp., and Cyclospora spp.) and six genera of helminths ( Trichuris spp., Strongyloides spp., Ascaris spp., Physaloptera spp., Ancylostoma spp., and Enterobius spp.). The overall sample prevalence of parasitic infection was 54.1% (1811/3349). Entamoeba spp. was the most prevalent (36.4%, 1218/3349). The infection rate was the highest in free-range animals (73.0%, 670/918) (P < 0.01) and Guangxi Zhuang autonomous region (64.8%, 566/873). Mixed infections were mostly detected for Entamoeba spp., Trichuris spp., and Strongyloides spp.. Molecular characterization was reviewed of Enterocytozoon bieneusi, Giardia duodenalis, Cryptosporidium spp., and Entamoeba spp., as these are zoonotic species or genotypes. This parasitological data for NHPs in China, provides important information for veterinarians and public health authorities for the elimination of such parasites and monitor the potential transmission of zoonotic infections from NHPs. Graphical abstract: Highlights: The first comprehensive survey of the intestinal parasites in NHPs. There were eleven genera of intestinal parasites were detected. The overall prevalence of parasitic infection was 54.1%. Review on the molecular characterization of the intestinal protozoans.